2014
DOI: 10.1016/j.rppneu.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between exercise performance in asthmatic children and healthy controls – Physical Activity Questionnaire application

Abstract: Despite the fact that a majority of the parents of allergic children stated that their child's disease was a barrier to physical activity, in our study there seems to be no difference between the level of physical activity of controlled asthmatic children and their healthy peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
9
0
5
Order By: Relevance
“…Some studies compared the physical activity levels between children and adolescents with CA and healthy subjects and concluded that, although most parents of children with asthma have reported a decrease in the performance of physical activities, the results showed that the level of physical activity was similar between the two groups and that there was no difference between children with and without asthma. 22,23 These studies show the gap between parents' and children's opinions of physical activity; therefore, we emphasize the importance of assessing physical activity level with answers obtained from the children, which is why we performed this study by questioning children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies compared the physical activity levels between children and adolescents with CA and healthy subjects and concluded that, although most parents of children with asthma have reported a decrease in the performance of physical activities, the results showed that the level of physical activity was similar between the two groups and that there was no difference between children with and without asthma. 22,23 These studies show the gap between parents' and children's opinions of physical activity; therefore, we emphasize the importance of assessing physical activity level with answers obtained from the children, which is why we performed this study by questioning children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies were performed in Europe, 4,[25][26][27][28][29][30][31][32][33][34][35][36] seven in South America, [37][38][39][40][41][42][43] five in North America, [44][45][46][47][48] and three in Asia. [49][50][51] Twenty-five had cross-sectional designs, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,[48][49][50]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The sample size varied from 19 37 to 426 51 participants with asthma, and the studies included 1668 boys and 1125 girls with asthma. Age varied from 5.1 ± 0.7 years 30 to 15.6 ± 0.5 years, 36 with 19 studies with mean age over 10 years, [26][27][28][29][32][33][34][35][36][37]39,41,42,45,[47][48][49][50][51] and two authors did not reported. 31,40 Forced expiratory volume in the first second (FEV 1 ) varied from 84.4 ± 3.5% to 104 ± 12.5%, and body mass index (BMI) varied from 15.8 ± 1.4 to 22.2 ± 4.8 kg/m 2 .…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Desde hace varios años se ha documentado que la actividad física y el deporte pueden tener repercusiones positivas en el estado de salud en general o un impacto importante en la calidad de vida de personas con enfermedades crónicas como depresión, artritis, asma, hipertensión o diabetes (21)(22)(23)(24)(25). Ha habido al respecto precaución y temor de recomendar actividad física en las personas con epilepsia, probablemente por la suposición de que dicha actividad pudiera desencadenar crisis epilépticas y que la aparición de las mismas pueda generar lesiones físicas.…”
Section: ¿Qué Efectos Clínicos Puede Tener La Actividad Física O El Dunclassified